The Factors that Influence the Acquisition of English Language by Yemeni KG2 Students - Muftah, Muneera Yahya Ali (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2017)
This study will investigate the internal as well as the external factors that influence the acquisition of English language by Yemeni kindergartens (KG2) students. To achieve its objectives, some different activities have been used to find out new styles to teach English language to the children at the age of 4-6 years old at three different kindergartens instruction phases. Findings show that Age and Motivation are the most important factors that affect the learning of a second languageÂ  in spite of the fact that there are some other important factors, either internal or external, that affect the learning process.